Motivasi Tokoh Takako Otomichi Sebagai Seorang Polisi Wanita Unggulan Dalam Novel Kogoeru Kiba Karya Asa Nonami - Feri Kartiana, Gede; Oeinada, I Gede; Damayanti, Silvia (Humanis; Volume 17. No. 1. Oktober 2016, 2016)
This study is entitled " Motivation of Character Takako Otomichi, as a Superior Policewoman Featured in Kogoeru Kiba Novel written by Asa Nonami". This study aims to determine the psychological state and the motivation of Takako Otomichi as the main character in the novel to become a superior policewoman in the Tokyo Metropolitan Police Department. The theory used in this research is the Sigmund Freud's theory of psychoanalysis (in Suryabrata, 1988:145-1490 as well as Abraham Maslow’s theory of Motivation needs (in Sutrisno, 2009:122-124). The method used in analyzing the data is descriptive analysis method. As the results of the analysis, the psychology of Takako Otomichi which consisted of the id, ego and superego are in balance. The Id of Takako Otomichi contains her desire to become a superior policewoman, the ego controls the id while superego acts according to the existing norms.In this study, Takako Otomichi as the main character is motivated by five levels of needs: firstly (1) Physiological need makes Takako Otomichi works as a policewoman in order to earn a living so that she can meet her basic needs. Secondly (2) The need for security encourages her to join the police force, therefore Takako Otomichi can get various facilities such as health insurance and annuities. Thirdly (3) The need for social relationship encourages Takako Otomichi to marry the man of her choice. Fourthly (4) The need for recognition makes Takako Otomichi to be motivated to pursue the perpetrators, thus her success can be recognized by her colleagues. The fifth (5) The need for self-actualization encourages Takako Otomichi to work hard and diligently, so that she can be a reliable police detective who devotes her ability for public safety.